INTRODUCTION OF MARKET ORIENTATION TYPES IN PROCESS DEVELOPMENT FACILITIES USING BRAND MANAGEMENT AND BRAND PERFORMANCE - Edward Wilson Gozali; Yolanda Masnita (Bussman Journal : Indonesian Journal of Business and Management, 2023)
The aim of this study is to find out how market orientation types facilitate the development of brand management processes (management strategic brand and internal brand), and brand performance. using data collected from brand executives. The results of this study indicate that proactive and reactive market orientations influence internal branding and strategic brand management. The mediating role of strategic brand management in the relationship between internal orientation mediates the relationship between PMO and brand performance. Also, strategic brand management and internal branding mediate the relationship between responsive market orientation (RMO) and brand performance. Results also show that market turbulence negatively moderates the relationship between strategic brand management and brand performance. Limitations/research implications – Building on the literature from brand management, organizational capabilities and market orientation, this study describes the role of PMO and RMO in influencing strategic brand management and different internal brands, and subsequently, brand performance. The perspectives used in this research provide insight into how organizations can develop and manage brands from a process perspective